2016
DOI: 10.1017/s1743921317001004
|View full text |Cite
|
Sign up to set email alerts
|

Photoionization models of Planetary Nebulae

Abstract: Abstract. The understanding of astronomical nebulae is based on observational data (images, spectra, 3D data-cubes) and theoretical models. In this review, I present my very biased view on photoionization modeling of planetary nebulae, focusing on 1D multi-component models, on 3D models and on big database of models.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…In our case, the n e ([Fe III]) = 10790 +3230 −2620 cm −3 we obtain for the low res-olution spectrum is rather close to the density of HH 204. This confirms the importance of the warning given by Morisset (2017) who, through photoionization models, predict large errors in the determination of the physical conditions and chemical abundances in nebulae if one assumes a single component when, in fact, there are several and some of them is composed by high-density gas. The exercise we present in this section is an observational confirmation.…”
Section: The Effects Of Lowering the Spatial And Spectral Resolutionsupporting
confidence: 73%
“…In our case, the n e ([Fe III]) = 10790 +3230 −2620 cm −3 we obtain for the low res-olution spectrum is rather close to the density of HH 204. This confirms the importance of the warning given by Morisset (2017) who, through photoionization models, predict large errors in the determination of the physical conditions and chemical abundances in nebulae if one assumes a single component when, in fact, there are several and some of them is composed by high-density gas. The exercise we present in this section is an observational confirmation.…”
Section: The Effects Of Lowering the Spatial And Spectral Resolutionsupporting
confidence: 73%
“…All the elements except for Ar have higher ICFs in the polar direction and lower in the equatorial region ( Figure 10). 3D photoionization models have demonstrated that the ICFs vary within the nebula (Morisset 2017). Moreover, it has also been suggested that a correction on the ICFs may be needed when we deal with non-spherical nebulae (Gonçalves et al 2012) and Abell 14 is one of these cases.…”
Section: Ionic and Total Abundancesmentioning
confidence: 99%